2018
DOI: 10.1177/0143034318807959
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence as a moderator between perfectionism and happiness

Abstract: Happiness plays a key role in influencing adolescent performance in a variety of contexts. The present study was designed to investigate the relationships between perfectionism, emotional intelligence, and happiness and to test the moderating role of emotional intelligence in the relationship between perfectionism and happiness among Malaysian adolescents. The participants were 412 Malaysian high-school students from Selangor, all of whom completed self-report questionnaires. Structural equation modeling (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The degree to which our own emotions are perceived positively affects the level of psychological and social adjustment (Palomera et al, 2012), and although concerns do not, high personal standards do help in solving problems (Gong et al, 2017). In addition, Emotional Intelligence acts as a moderator of perfectionism and happiness (Abdollahi et al, 2019) of perfectionism and loneliness (Kaya & Birol, 2018), of maladaptive perfectionism and anxiety (Abdollahi & Abu-Talib, 2015) as well as between Perfectionistic Strivings and Concerns and depression and anxiety (Smith et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which our own emotions are perceived positively affects the level of psychological and social adjustment (Palomera et al, 2012), and although concerns do not, high personal standards do help in solving problems (Gong et al, 2017). In addition, Emotional Intelligence acts as a moderator of perfectionism and happiness (Abdollahi et al, 2019) of perfectionism and loneliness (Kaya & Birol, 2018), of maladaptive perfectionism and anxiety (Abdollahi & Abu-Talib, 2015) as well as between Perfectionistic Strivings and Concerns and depression and anxiety (Smith et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…First, the study of EI in adolescents faces the challenge of scarce investigation about its relationship with happiness, optimism, and pessimism. Few studies evaluated EI with SWB (Abdollahi et al, 2019;Lim et al, 2015;Sánchez-Álvarez et al, 2015;Serrano & Andreu, 2016); among them, only three examined specifically the three EI dimensions rather than the general construct of EI in relation to SWB (Extremera et al, 2007;Gascó et al, 2018;Serrano & Andreu, 2016), only one focused on the relationship of EI with happiness (Serrano & Andreu, 2016), and only one investigated EI with optimism and pessimism (Extremera et al, 2007).…”
Section: Current Challenges In the Study Of Ei In Adolescencementioning
confidence: 99%
“…Research accumulated evidences about the existing relationship between EI and SWB (Abdollahi et al, 2019;Abdollahi et al, 2015;Chamorro-Premuzic et al, 2007;Gascó et al, 2018), which is defined by a cognitive component (i.e., life satisfaction) and an affective component (i.e., happiness) (Tomlinson et al, 2017). Studies investigating happiness and its relationship with EI to promote greater psychological development are considered valuable, especially during adolescence (Abdollahi et al, 2019). In their longitudinal study, Sánchez-Álvarez et al (2015) showed that EI was positively associated to SWB over time.…”
Section: The Relationship Of Ei With Happinessmentioning
confidence: 99%
See 2 more Smart Citations